Advanced Characterization and On-Line Process Monitoring of Additively Manufactured Materials and Components - Bruno, Giovanni; Maierhofer, Christiane (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is concerned with the microstructural characterization and the defect analysis of metallic additively manufactured (AM) materials and parts. Special attention is paid to the determination of residual stress in such parts and to online monitoring techniques devised to predict the appearance of defects. Finally, several non-destructive testing techniques are employed to assess the quality of AM materials and parts.